Determinants of nonresident government debt ownership. Issue 2 (19th January 2017) - Afonso, António; Silva, Jorge
ABSTRACT: We examine the determinants of nonresident government debt ownership, accounting for domestic and external factors and financial variables during the period 2000Q2–2014Q4, focussing on a small euro area open economy: Portugal. Our results show that better fiscal positions, higher systematic stress in Europe and higher shares of monetary and financial institutions (MFI) cross-border holdings of public debt, increase the share of nonresident held debt, and rising sovereign yields decrease that ratio.